ANALISA KUALITAS SUARA JARINGAN VOIP BERBASIS PROTOKOL SIP (Information Technology and Telematics, 2014)
 Abstract Voice over Internet Protocol technology, or better known as VoIP, is a technology that can change the information in the form of a voice in the form of analog signals into digital signals that can be passed to a computer network. In the process of these changes, there are several kinds of codecs with different characters - different. With the several different kinds of codecs, it is necessary to know the impact of the use of the codec network quality and sound quality delivered through a VoIP network. To determine the quality of a VoIP network that includes bandwidth, delay jitter and packet loss using Ethereal program. As for knowing the quality of sound as sound intensity, noise and the frequency of the sound that is sent through a VoIP network using the program Cool Edit Pro. With the selection of the appropriate codec with network conditions, it can produce good quality VoIP communication keyword : VoIP, VoIP network performance, VoIP sound quality